Recalculando rotas : uma etnografia sobre trânsitos de corpos, afetos e sexualidades em vivências transmasculinas - Sofia Gonçalves Repolês (2017)
This dissertation is about bodies and affections that go through ways and routes of life marked by transidentification with masculinities. It is an effort to map possibilities and strategies for transmasculine living and resisting, which give rise to multiples corporalities and gender identification in a world mediated for cisgender and heterosexual standarts. Our objective was to comprehend, always partially, how transidentification produces effects in our relations with ourselves and our bodies as well in sexual/affective relations and in our sexual practices and desires. For this, semi structured interviews were conducted, as well as fieldwork in events such as meetings, talkgroups and others activities done for and by people who experience transmasculinities, between 2015 and 2017. The researcher body transits, subjectivity and gender are also brought to the text as constituent elements of the research and concomitantly constituted by it. These presented here by means of analytics and reflexives elements about the processes of transidentification and affection that were produced in field and on the relations with the partners.